2020
DOI: 10.1161/circulationaha.120.050749
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Adding Ticagrelor to Standard Aspirin on Saphenous Vein Graft Patency in Patients Undergoing Coronary Artery Bypass Grafting (POPular CABG)

Abstract: Background: Approximately 15% of saphenous vein grafts (SVGs) occlude during the first year after coronary artery bypass graft surgery (CABG) despite aspirin use. The POPular CABG trial investigated whether ticagrelor added to standard aspirin improves SVG patency at one year after CABG. Methods: In this investigator-initiated, randomized, double-blind, placebo-controlled, multicenter trial, patients with ≥1 SVGs were randomly assigned (1:1) after CABG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 35 publications
0
54
2
1
Order By: Relevance
“…38 Furthermore, Zhao et al (2018) 39 reported improved graft patency with ticagrelor and aspirin when compared to aspirin alone, however this was not accompanied with a statistically significant difference in MACE or MI. This contrasts the data from the POP-CABG trial 40 which found no difference in SVG occlusion rates in 499 patients after a year of DAPT with ticagrelor (compared to aspirin and placebo).…”
Section: Secondary Prevention After Surgerycontrasting
confidence: 99%
“…38 Furthermore, Zhao et al (2018) 39 reported improved graft patency with ticagrelor and aspirin when compared to aspirin alone, however this was not accompanied with a statistically significant difference in MACE or MI. This contrasts the data from the POP-CABG trial 40 which found no difference in SVG occlusion rates in 499 patients after a year of DAPT with ticagrelor (compared to aspirin and placebo).…”
Section: Secondary Prevention After Surgerycontrasting
confidence: 99%
“…However, this benefit was not confirmed in another newly published randomized study on the same topic. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DAPT was associated with a 31% higher risk of bleeding in the overall study population. It is noteworthy that almost all of the studies involved were designed to evaluate the efficacy of DAPT on graft patency rather than its effects on clinical outcomes, were underpowered, 15 , 16 , 23 had substantially heterogeneous populations, 14 , 40 and used different DAPT definitions, thereby precluding conclusive inference and resulting in inconsistent guideline recommendations 2 , 24 , 25 and variation in real‐world clinical practice patterns. 41 …”
Section: Discussionmentioning
confidence: 99%
“…The recently completed POPular‐CABG RCT also evaluated the addition of ticagrelor to aspirin in post‐CABG patients but found no difference in SVG patency at 1‐year 50 . Although an important difference with the POPular‐CABG and DACAB trials were the dose of aspirin (80 and 100 mg, respectively), this did not have the expected effect on patency rates (~91% and ~77%, respectively).…”
Section: Antiplatelet Therapymentioning
confidence: 99%